2016
DOI: 10.7567/apex.9.111102
|View full text |Cite
|
Sign up to set email alerts
|

Growth of rocksalt-structured MgxZn1− xO (x > 0.5) films on MgO substrates and their deep-ultraviolet luminescence

Abstract: Single-phase rocksalt-structured Mg x Zn1− x O (x > 0.5) alloy films were grown on MgO substrates using the mist chemical vapor deposition method. A specular surface with a step and terrace structure was obtained. The bandgap was tuned from 5.9 to 7.8 eV as x varied from 0.5 to 1. Deep ultraviolet cathodoluminescence, stemming from near band edge transitions, was observed for Mg0.57Zn0.43O in the 4.8–5.5 eV rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…In previous studies, we reported the epitaxial growth of NiO thin films on α-Al2O3 substrates via mist chemical vapor deposition (CVD) [7]. By this method, highquality oxide thin films can be grown at atmospheric pressure and semiconductor alloy crystals such as MgxZn1-xO [8,9] and (AlxGa1-x)2O3 [10] can be easily obtained by mixing precursor source solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we reported the epitaxial growth of NiO thin films on α-Al2O3 substrates via mist chemical vapor deposition (CVD) [7]. By this method, highquality oxide thin films can be grown at atmospheric pressure and semiconductor alloy crystals such as MgxZn1-xO [8,9] and (AlxGa1-x)2O3 [10] can be easily obtained by mixing precursor source solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have succeeded in growth of atomically flat RS-MgZnO thin films on MgO substrates by the mist chemical vapor deposition (mist CVD) method. [17][18][19] The epitaxial films exhibited cathodoluminescence (CL) peaks located in a range from 5.09 eV (4.91 eV) at 6 K (300 K) for x ¼ 0.61 to 6.24 eV (6.05 eV) at 6 K (300 K) for x ¼ 0.95. [15,[17][18][19][20] The energy difference between the E g and CL peak positions is defined as the Stokes-like shift.…”
mentioning
confidence: 99%
“…[17][18][19] The epitaxial films exhibited cathodoluminescence (CL) peaks located in a range from 5.09 eV (4.91 eV) at 6 K (300 K) for x ¼ 0.61 to 6.24 eV (6.05 eV) at 6 K (300 K) for x ¼ 0.95. [15,[17][18][19][20] The energy difference between the E g and CL peak positions is defined as the Stokes-like shift. The origin of the relatively large Stokes-like shift of 0.8-0.9 eV is a debatable issue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported DUV emissions from rocksalt MgZnO films at the peak energies of 4.88-5.21 eV in their cathodoluminescence (CL) spectra at low temperatures below 100 K. 12,13) However, besides the DUV emissions, unintended UV and blue emission peaks were observed. It was hard to obtain pure DUV emission especially at room temperature (RT).…”
mentioning
confidence: 99%